O patrimônio cultural e gráfico: inventário de identidades visuais da indústria de Ijuí/RS do século XX - Souza, Fabricio de (2024)
Reflecting on cultural heritage and design brings us closer to a common characteristic of these areas: identities. In this study, the inventory of graphic assets is related to the visual identities of the industry in Ijuí/RS, a city located in the northwest of Rio Grande do Sul, which throughout the 20th century faced the expansion of commerce and factory production, occurring at a time when there was already a regional and national consumer market. These industries needed to be identified due to market needs, leading each sector to gain an identity according to what was offered to its public. The consultation takes place in the documentary collection safeguarded by the Museu Antropológico Diretor Pestana, part of the Ijuí Collection, which maintains records of part of this visual memory in materials corresponding to the city's economy. From the delimited temporal cut and the identification of where to locate such records, a methodology was established to assist in the construction of an inventory form to develop analyses related to the visual identities of the industry in Ijuí, enabling the construction of a catalog that will gather information on this investigated theme. The methodology identified as "Research in History of Design from Printed Materials Collections" aided in discussions and reflections related to the recognition and valorization of local graphic heritage, presenting them as artifacts that reflect the identities of the time and place in which they were produced. The catalog, which gathers information and presents the research results materialized through the Graduate Program in Cultural Heritage (UFSM), in the Research Line of History and Cultural Heritage, highlights the concentration of analyses regarding the visual identities of the eleven industries of Ijuí/RS from the 20th century, duly identified based on conceptual classifications of brands, referencing their history and emphasizing their connection with the local production context.